1974
DOI: 10.1021/jf60196a002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of pigments from protein-carbonyl browning systems. Models for two insulin-glucose pigments

Abstract: Limit-peptide pigments of approximately 7800 and 1500 molecular weight were isolated from a humidified insulin-glucose-U-14C reaction system. Gel chromatographic analysis of the intact model system and analyses of the amino acid and carbohydrate compositions of the limit-peptide pigments indicated cross-linking between peptide chains. This cross-linking was associated with extensive condensation of sugar residues, some of which have already reacted with amine groups on the protein, into aggregates of up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 15 publications
4
17
0
2
Order By: Relevance
“…Hofmann (1998) reported that the reaction between casein and glucose led to a drastic increase in the MWs by carbohydrate-induced oligomerisation of the protein backbone. Furthermore, these results confirm the earlier findings of Clark and Tannenbaum (1974) that the reaction between proteins and carbohydrates leads to polymerisation of the reaction mixture. The results showed that the shapes of the chromatogram of MRPs derived from the Glu-Di and Glu-Tri model systems were different from those of MRPs derived from the Glu-G model system as the heating time increased.…”
Section: Evolution Of Mw In Mrpssupporting
confidence: 91%
“…Hofmann (1998) reported that the reaction between casein and glucose led to a drastic increase in the MWs by carbohydrate-induced oligomerisation of the protein backbone. Furthermore, these results confirm the earlier findings of Clark and Tannenbaum (1974) that the reaction between proteins and carbohydrates leads to polymerisation of the reaction mixture. The results showed that the shapes of the chromatogram of MRPs derived from the Glu-Di and Glu-Tri model systems were different from those of MRPs derived from the Glu-G model system as the heating time increased.…”
Section: Evolution Of Mw In Mrpssupporting
confidence: 91%
“…Hofmann (29) reported that the reaction between casein and glucose led to a drastic increase in molecular weights by carbohydrate-induced oligomerization of the protein backbone. Furthermore, these results confirm the earlier findings of Clark and Tannenbaum (30) that the reaction between proteins and carbohydrates leads to polymerization of the reaction mixture. The results showed that the melanoidins formed from BG after different thermal processing steps had different size exclusion chromatography elution patterns.…”
Section: Resultssupporting
confidence: 91%
“…Other tissues that contain long-lived proteins, such as lens and nerve, might be affected by nonenzymatic browning as well. Isolation and structural analyses of protein pigments are required to further substantiate the browning concept and indicate more specifically how these modified proteins might play a role in the pathogenesis of the complications of diabetes and aging (31)(32)(33). In addition, further understanding of nonenzymatic browning in vivo is needed so that strategies for interfering with the process on long-lived proteins can be devised.…”
Section: Discussionmentioning
confidence: 99%